Criminological Study of Crime in Ambon City with Island Characteristics - Hahury, Charly Timothy; Titahelu, Juanrico Alfaromona Sumarezs; Leasa, Elias Zadrack (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: Ambon City as the center of government, education and economy in Maluku, has also developed into a center for various crimes. This is due to the support of the geographical location of Ambon City and Maluku as a whole as an Island Province. The problem in this writing is how are the characteristics of crime in Ambon City which is characterized by an island and how are efforts to overcome crime in Ambon City which is characterized by an island.Purposes of the Research: The purpose of this writing is to study and analyze the characteristics of crime in Ambon City which is characterized by an island and to study and analyze efforts to overcome crime in Ambon City which is characterized by an island.Methods of the Research: The research method used is empirical juridical, the data sources used are primary data and secondary data. Data collection techniques through observation, interviews and literature studies. Qualitative data analysis techniques.Findings of the Research: The results of the study show that the characteristics of crime in Ambon City which is characterized by an island are divided into 3 groups, namely conventional crimes that stand out are aggravated theft; transnational crimes that stand out are narcotics trafficking crimes; and crimes based on social conflict involving areas/regions that have long been in conflict. Efforts to combat crime in Ambon City begin with identifying the factors that cause crime and linking them to the criminology theories used, after which two approaches are used, namely the penal approach and the non-penal approach to combat various crimes.